Constructing 'the ethical' in the development of biofuels - Smith, Robert David Jonathan (2016)
In the past fifty years, calls to address the ethical and social dimensions in the biosciences have become pervasive. To this end, notions of bioethics, and an associated range of methodologies have been institutionalised throughout the UK biosciences; talk of research ethics, public engagement, various forms of technology assessment, and recently notions of responsible innovation in technoscientific worlds is increasingly commonplace. A desire to unpack discourse and action surrounding these practices sits at the heart of this thesis. Of particular interest are the ways that different groups construct the ethical dimensions of biofuel development and deployment and then distribute responsibility for addressing them. To achieve this, I find analytic power by deploying theory from the interpretative social sciences, namely the sociology of bioethics and science and technology studies. Empirically, I use controversy about the development and deployment of biofuels as a means to analyse, primarily through documentary analysis and qualitative interview, how three prominent groups (non-governmental organisations, public research funders and scientists) construct understandings of ethics and then distribute responsibility for addressing those issues. This approach makes it possible to see that the constitution of ethical issues (their ‘form’) and the ways that they are addressed (the ‘task’ of ethics) are both tightly coupled to the situations from which they arise. They are thus fundamentally multiple, locally contingent and often unpredictable. Using a range of discursive strategies and actions, actors are able to negotiate, blurring in and out of focus, what counts as an appropriate issue of concern, who should be addressing it and how. Dominant traditions of theory and practice have a tendency to standardise the form and task of ethics, such as in terms of issue types (e.g. ‘Playing God’) and the methods for addressing them (e.g. public engagement). I argue that situated nature of ethical dimensions should be acknowledged rather than ignored and that doing so is fundamental to making research more ‘socially robust’. However, this tension between dominant institutionalised forms and lived experiences is not easily resolved because it forces an engagement with the roles of those who are tasked with steering knowledge production. Hope is, however, offered by new approaches that have explicitly sought to deal with such tensions in new forms of knowledge production and new models of collaboration.